Development of a Core Outcome Set for Dysphagia Interventions in Parkinson's Disease: the COS-DIP Study - Hirschwald, Julia Antonia (Trinity College Dublin. School of Linguistic Speech & Comm Sci. Discipline of Clin Speech & Language Studies, 2025)
Introduction: Current clinical trials on oropharyngeal dysphagia (OD) in Parkinson's disease (PD) use a wide range of outcomes and different outcome measurement instruments (OMIs) making comparative effectiveness research challenging and limiting the evidence base for OD interventions in PD. Furthermore, the views of people with the health condition and dysphagia clinicians when selecting trial outcomes have not been previously considered, thus study results may be of little importance to them. The aim of this thesis was to develop an agreed, standardised Core Outcome Set for Dysphagia Interventions in Parkinson's disease (COS-DIP) by agreeing core outcomes and definitions, OMIs and timepoints of measurement for each core outcome. Methods: The study was prospectively registered with the Core Outcome Measures in Effectiveness Trials (COMET) database (www.comet-initiative.org, registration number: 1942). Full ethical approval was obtained from the university's local ethics committee. A study protocol outlining the planned methodology for the development of the COS-DIP was written and published open access. This included developing a long list of outcomes for OD intervention studies in PD. First, a scoping review was conducted to identify currently measured OD intervention outcomes in PD. Next, online surveys and focus groups with people with OD in PD, family members/caregivers, and dysphagia clinicians assessed perspectives on what is considered important to measure in these studies. The long list of outcomes was then used in a three-round online Delphi survey and subsequent consensus meetings with all key stakeholders (i.e., people with OD in PD, family members/caregivers, healthcare professionals and researchers) to agree the core outcomes, their definitions, OMIs, and timepoints of measurement. Results: The long list of outcomes comprised of 45 outcomes based on the scoping review, online surveys and focus groups. Participants in the Delphi survey and consensus meetings agreed on six core outcomes to be measured as a minimum in OD intervention studies in PD: `penetration/aspiration', `aspiration pneumonia', `choking', `OD severity', `swallowing related quality of life' and `post swallow pharyngeal residue'. Consensus was also reached on the definitions and OMIs for each core outcome. Timepoints of measurement were agreed to be a minimum pre, immediately post and 3-months post completion of the intervention. In addition, advisable timepoints of measurement were agreed to be 1-month pre and 6- and 12-months post completion of the intervention. Conclusions: Consistently using the COS-DIP in future OD intervention studies in PD will help ensure that these studies measure the aspects of OD in PD that are most important to all key stakeholders and will facilitate comparative effectiveness research. This will improve the quality of the evidence available to inform clinical decision-making, ultimately leading to better outcomes for people with OD in PD. Regular evaluation of the COS-DIP is crucial to ensure its continued validity and relevance. This ongoing assessment will determine whether the selected outcomes continue to be important to all key stakeholders and will provide opportunities to refine the COS-DIP by adding or removing outcomes and OMIs or revising definitions and timepoints of measurement. Monitoring the uptake and reporting of the COS-DIP in relevant studies will be essential for assessing its impact on research quality.
APPROVED
Keywords: dysphagia; Parkinson's disease; Core Outcome Set